THE REFLECTION OF HEALTHCARE INFORMATICS SYSTEMS ON NURSING PRACTICES - Merdiye Şendir; Hamiyet Kızıl; Semra Açıksöz (Sakarya University, 2019)
Nursing is an applied science. Technology influences and determines practices. Accordingly, it is necessary to know how information technologies affect nursing, and how they might change nursing practices, reduce nursing workload and affect information systems. By using computers, nurses can provide a more individualized nursing care, and they can train and give counseling to healthy or diseased individuals. Moreover, patient records are used by all members of the healthcare team as tools of communication, training, identification, research, legal documentation, supervision and control. It is important to record nursing care both legally and professionally. Computer-based informatics systems help to document nursing care practices in healthcare settings and clinical centers. In this context, it is necessary to know information and communication technologies influencing nursing practices. This study was conducted to evaluate the research studies examining the use of healthcare informatics systems and their effects on nursing practices and to identify the types of research studies needed in this field.